Israel, the land and the people an evangelical affirmation of God's promises - House, H. Wayne (Grand Rapids, MI Kregel, 1998)
Includes bibliographical references and indexes.
Keywords: Israel (Christian theology).; Christianity and other religions -- Judaism; Judaism -- relations -- Christianity; Covenants -- religious aspects -- Christianity